Muros de papéis e cortinas de ferro : a (in)visibilidade de gênero em processos jurídicos no interior do estado do Mato Grosso - Silva, Thamyres Müller (2022)
This paper presents an analysis of the social experiences of transgender women in legal cases and how they develop from these experiences, with a specific focus on two lawsuits that circulated in the legal sector of the interior of the state of Mato Grosso, bringing the narratives of the parties that integrate the processes and the anthropological analysis of the verification of how the cultural construction of the social roles of masculine and feminine reflect in the resolution of the lawsuits by the enforcers of the law, emphasizing the norms or lack of them for the guarantee of their fundamental rights, gender identity, right to equality, freedom and right to recognition and use of the social name, as well as how these dialogues are presented and structured in different ways to the treatment that is given to these subjects of law. Addressing for that the binary system of male and female and the recognition or not of the judiciary in the face of gender diversity and consequently the social representations that involve them, we discuss what are the side effects of not using the social name and what spaces permeate transsexual women within the prison establishment within the state. The text is structured in three parts. In the first chapter the context is purely ethnographic with the use of the concepts and anthropological analyses verified regarding gender, transsexuality and social name. The second and third parts were written based on the documental analysis of the two aforementioned legal cases, based on documental ethnography, in which we tried to bring the procedural narratives together with the anthropological debates about the theme. In light of this procedural analysis, we expanded the theories of gender and how the processes of identification and social construction are constructed, resulting in a vision beyond the roles that are attached to the records.